Differential Protein Distribution between the Nucleus and Mitochondria: Implications in Aging - Lionaki, Eirini; Gkikas, Ilias; Tavernarakis, Nektarios (Frontiers in Genetics, 2016)
The coordination of nuclear and mitochondrial genomes plays a pivotal role in maintenance of mitochondrial biogenesis and functionality during stress and aging. Environmental and cellular inputs signal to nucleus and/or mitochondria to trigger interorganellar compensatory responses. Loss of this tightly orchestrated coordination results in loss of cellular homeostasis and underlies various pathologies and age-related diseases. Several signaling cascades that govern interorganellar communication have been revealed up to now, and have been classified as part of the anterograde (nucleus to mitochondria) or retrograde (mitochondrial to nucleus) response. Many of these molecular pathways rely on the dual distribution of nuclear or mitochondrial components under basal or stress conditions. These dually localized components usually engage in specific tasks in their primary organelle of function, whilst upon cellular stimuli, they appear in the other organelle where they engage in the same or a different task, triggering a compensatory stress response. In this review, we focus on protein factors distributed between the nucleus and mitochondria and activated to exert their functions upon basal or stress conditions. We further discuss implications of bi-organellar targeting in the context of aging.